Optimization of Dye and Plasticizer Concentrations in Halochromic Sensor Films for Rapid pH Response Using Bird-Inspired Metaheuristic Algorithms - Daeuk Kim; Ronnie S. Concepcion; Joseph Rey H. Sta. Agueda; Jubert C. Marquez (Sensors)
The pH level of a wound environment is a crucial biomarker for monitoring wound healing, particularly in chronic wounds, where alkalinity (pH > 7) is linked to bacterial colonization and infection. This study developed and optimized a halochromic sensor film composed of polyvinyl alcohol (PVA), polyethylene glycol (PEG), and bromothymol blue (BTB) to enable rapid and reliable pH-responsive color transitions. Feature selection using Principal Component Analysis (PCA) and the ReliefF algorithm identified Hue, Saturation, and a as key features influencing pH responsivity. Optimization of BTB (0.01–0.05%) and PEG (6–10%) concentrations was conducted using bird-inspired metaheuristic algorithms, including the Parrot Optimizer (PO), Pelican Optimization Algorithm (POA), and Secretary Bird Optimization Algorithm (SBOA). While final fitness values showed negligible variation (188.595647 for GP-PO, 188.595634 for GP-POA, and 188.595634 for GP-SBOA), GP-PO demonstrated superior convergence and stability, efficiently identifying the optimal formulation (0.02% BTB, 6% PEG). The optimized film achieved a complete color transition within 3–5 min, a 23.15% reduction compared to the non-optimized formulation. Statistical analysis revealed that BTB concentration significantly affected response time (p = 0.01), while PEG concentration had no significant effect (p > 0.05). These findings highlight the potential of halochromic films for real-time, non-invasive pH monitoring in chronic wounds.